2020
DOI: 10.1038/s41598-020-63948-y
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of ovaries with collagenase before vitrification keeps the ovarian reserve by maintaining cell-cell adhesion integrity in ovarian follicles

Abstract: the mammalian ovarian follicle is comprised of the germ cell or oocyte surrounded by the somatic cells, the granulosa and theca cells. the ovarian stroma, including the collagen-rich matrix that supports the three-dimensional disk-like follicular structure, impacts the integrity of the ovarian follicle and is essential for follicular development. Maintaining follicular integrity during cryopreservation has remained a limiting factor in preserving ovarian tissues for transplantation because a significant propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Ovarian tissue vitrification is known to promote an atretic process in most follicles, except primordial follicles, which are known to better tolerate cryopreservation injury due to their unique structure [ 17 ]. Consistent with past studies [ 18 ], in the current study we also showed that the primordial follicles were mostly well protected in all study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tissue vitrification is known to promote an atretic process in most follicles, except primordial follicles, which are known to better tolerate cryopreservation injury due to their unique structure [ 17 ]. Consistent with past studies [ 18 ], in the current study we also showed that the primordial follicles were mostly well protected in all study groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dehydration for 10 min led to decrease in the expression of genes enriched in functional terms related to cadherins, cell-cell adhesion factors that play important roles in membrane fusion. Such disturbance in cell-cell adhesion and communication may be a result of exposure to the high osmotic solution during preservation process [ 53 ], and a recent study has shown that the addition of collagen before the exposure to vitrification solution improves viability of secondary follicles in the ovarian tissue [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fresh follicles were found to have higher levels of CX43 expression than vitrified follicles, and CX43 expression levels were also significantly lower in follicles cultured in vitro for 4 days ( Bus et al, 2021 ), therefore, preservation and promotion of communications in cultured follicles may increase their quality in IVM. Kawai and Shimada found that during vitrification, the attachment of the oocyte to CCs was impaired because of the loss of cadherin adhesion molecules, which was critical for AJs ( Kawai and Shimada, 2020 ). By treating ovaries briefly with collagenase before vitrification, they successfully preserved AJs and maintained the morphology of oocytes, suggesting a new potential approach for raising the functions and viability of cryopreserved ovaries.…”
Section: Applications Of Intercellular Communications and Future Pers...mentioning
confidence: 99%